Tata Cara Peningkatan Kinerja Karyawan pada SMAN 1 Peureulak Kabupaten Aceh Timur - Rianovitasari; M Djamil HS (Yayasan Kawanad, 2022)
This research aims to investigate procedures for improving employee performance at SMAN 1 Peureulak, East Aceh Regency. By applying both qualitative and quantitative approaches, this research investigates the implementation of strategies such as careful recruitment, ongoing training, motivation, and recognition for good performance. Data obtained through interviews, observations and questionnaires were analyzed to understand the impact on employee satisfaction, motivation and productivity. The results show that procedures for improving employee performance at SMAN 1 Peureulak provide positive results, creating a conducive work environment and increasing employee involvement. However, this research also identifies the potential for further development to ensure sustainability and improvement in employee performance management